Intervention and Public Policy Pathways to Achieve Health Care Equity - Shelley White-Means; Darrell J. Gaskin; Ahmad Reshad Osmani (International Journal of Environmental Research and Public Health, 2019)
Health care equity reflects an equal opportunity to utilize public health and health care resources in order to maximize one's health potential. Achieving health care equity necessitates the consideration of both quantity and quality of care, as well as vertical (greater health care use by those with greater needs) and horizontal (equal health care use by those with equal needs) equity. In this paper, we summarize the approaches introduced by authors contributing to this Special Issue and how their work is captured by the National Institute of Minority Health and Health Disparities (NIMHD) framework. The paper concludes by pointing out intervention and public policy opportunities for future investigation in order to achieve health care equity.
Keywords: H0; I1; 330; health care equity; NIMHD framework; interventions